OakRootRNADB—a consolidated RNA-seq database for coding and noncoding RNA in roots of pedunculate oak (Quercus robur). (17th November 2022) - Kościelniak, Paulina; Glazińska, Paulina; Zadworny, Marcin
Abstract: The degree to which roots elongate is determined by the expression of genes that regulate root growth in each developmental zone of a root. Most studies have, however, focused on the molecular factors that regulate primary root growth in annual plants. In contrast, the relationship between gene expression and a specific pattern of taproot development and growth in trees is poorly understood. However, the presence of a deeply located taproot, with branching lateral roots, can especially mitigate the effect of insufficient water availability in long-lived trees, such as pedunculated oak. In the present article, we integrated the ribonucleic acid (RNA) sequencing data on roots of oak trees into a single comprehensive database, named OakRootRNADB that contains information on both coding and noncoding RNAs. The sequences in the database also enclose information pertaining to transcription factors, transcriptional regulators and chromatin regulators, as well as a prediction of the cellular localization of a transcript. OakRootRNADB has a user-friendly interface and functional tools that increase access to genomic information. Integrated knowledge of molecular patterns of expression, specifically occurring within and between root zones and within root types, can elucidate the molecular mechanisms regulating taproot growth and enhanced root soil exploration. Database URL https://oakrootrnadb.idpan.poznan.pl/